2019
DOI: 10.1108/jhr-06-2018-0023
|View full text |Cite
|
Sign up to set email alerts
|

Female labor force participation, paid maternity, caste system and under-5 mortality in Nepal

Abstract: Purpose The under-5 mortality rate in Nepal remains high in comparison to neighboring countries and developed nations. The result of this problem on Nepal’s social, economic, political and cultural development makes it an urgent priority requiring the Nepalese Government to address this issue. The purpose of this paper is to find out if Nepal’s high female labor force participation (FLFP), the caste system and no paid maternity leave are contributing factors to under-5 deaths in Nepal. Design/methodology/app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…FLFP was associated with the reduction of both infant and U5MR. The inverse relationship between FLFP and child survival is consistent with a more recent study in Nigeria36 but contrast similar studies conducted in Nepal 37 38. Authors that found a negative impact of FLFP explained that mothers who are economically active and hold certain key positions in society may not have time for their children exposing them to series of life-threatening diseases and other environmental hazards 39…”
Section: Discussionsupporting
confidence: 85%
“…FLFP was associated with the reduction of both infant and U5MR. The inverse relationship between FLFP and child survival is consistent with a more recent study in Nigeria36 but contrast similar studies conducted in Nepal 37 38. Authors that found a negative impact of FLFP explained that mothers who are economically active and hold certain key positions in society may not have time for their children exposing them to series of life-threatening diseases and other environmental hazards 39…”
Section: Discussionsupporting
confidence: 85%
“…The highest female borrower rate was observed in Nepal, with almost 100% in some years. Social norms and cultural practices greatly influence Nepal's labor force (Timilsina, Sawangdee, Hunchangsith, & Rittirong, 2019). For example, due to the high international migration of Nepalese men, many women engage in livestock and agriculture (Sijapati, Bhattarai, & Pathak, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The Cox hazard analysis was conducted between dependent and independent variables as the preferred analysis to conclude the study. Cox hazard was preferred it take into consideration both risk to death under 3 years of age of children when concentrating on time in each month (Timilsina et al, 2019). The time variation here is measured by the current age of the child in months (months since birth for dead children).…”
Section: Discussionmentioning
confidence: 99%
“…Dependent variables of the study were chosen based on the fact that Nepal is developing country with high child mortality it ranks 67 th from below among 225 countries published by world fact book in 2017. Nepal also has very high child mortality if compared to its neighbor countries such as Bangladesh, Maldives, Sri Lanka and signi cantly higher if compared to developed countries like the USA, Singapore, UK (Timilsina et al, 2019).…”
Section: Model Speci Cationmentioning
confidence: 99%